Polymer-Based Shaping Strategy for Zeolite Templated Carbons (ZTC) and Their Metal Organic Framework (MOF) Composites for Improved Hydrogen Storage Properties - Molefe, Lerato Y.; Musyoka, Nicholas M.; Ren, Jianwei; Langmi, Henrietta W.; Mathe, Mkhulu; Ndungu, Patrick G. (Frontiers in Chemistry, 2019)
Porous materials such as metal organic frameworks (MOFs), zeolite templated carbons (ZTC), and some porous polymers have endeared the research community for their attractiveness for hydrogen (H2) storage applications. This is due to their remarkable properties, which among others include high surface areas, high porosity, tunability, high thermal, and chemical stability. However, despite their extraordinary properties, their lack of processability due to their inherent powdery nature presents a constraining factor for their full potential for applications in hydrogen storage systems. Additionally, the poor thermal conductivity in some of these materials also contributes to the limitations for their use in this type of application. Therefore, there is a need to develop strategies for producing functional porous composites that are easy-to-handle and with enhanced heat transfer properties while still retaining their high hydrogen adsorption capacities. Herein, we present a simple shaping approach for ZTCs and their MOFs composite using a polymer of intrinsic microporosity (PIM-1). The intrinsic characteristics of the individual porous materials are transferred to the resulting composites leading to improved processability without adversely altering their porous nature. The surface area and hydrogen uptake capacity for the obtained shaped composites were found to be within the range of 1,054–2,433 m2g−1 and 1.22–1.87 H2 wt. %, respectively at 1 bar and 77 K. In summary, the synergistic performance of the obtained materials is comparative to their powder counterparts with additional complementing properties.